Financial literacy: a peep into the literature and note for policy/ Alhassan Musah, Ibrahim Nandom Yakubu and Matthew Amalitinga Abagna - Musah, Alhassan; Yakubu, Ibrahim Nandom; Abagna, Matthew Amalitinga (Universiti Teknologi Mara Selangor, 2022)
This paper provides a review of the financial literacy literature mostly on definitional issues and some determinants. The paper also explores an emerging genre of research into financial literacy that emphasizes interconnectedness with society and financial systems, in general. The authors employ a literature review to examine the extant literature on the conceptual framework of financial literacy as well as empirical evidence on the causal relationship between financial literacy and efficient financial decision making. We argue that whilst the literature on financial literacy is growing it is far from being exhaustive, with substantial research outputs in other climes other than Africa. There is almost a tidy conclusion from the literature that young people and women are less likely to grasp basic financial concepts. The paper concludes by calling for a reconfiguration of research efforts in financial literacy to reflect context, and for policymakers to properly align the design of financial literacy programmes to meet the needs of key demographic segments in the short term, and to contribute to financial stability in the medium to long term.